The Islamic Law Perspective of Universitas Muhammadiyah Surakarta Pension Fund Management (Journal of Islamic Economic Laws, 2019)
Pension fund is one of the non-bank financial institutions that manages and implements program to generate retirement benefits. Pension fund is one of potential resources of fund which operation can be based on either conventional or Islamic principle. This research will focus on the type of contracts used by Universitas Muhammadiyah Surakarta (UMS) Pension Fund whether its operation conforms the requirements of shariah princple or not. This research aims to know, elaborate and evaluate the conformity of shariah principle in the UMS Pension Fund operation. The type of research carried out here is qualitative with the descriptive evaluative approach. The data is obtained through observation, documentation and interview. The result of the research shows that the contracts used in managing the fund by UMS Pension Fund are muḍārabah, wakalah, ijārah and hibah. Muḍārabah contract is used between the pension fund and the participants as well as between pension fund and investee. Wakalah contract is used between the employer which is UMS in this case and the pension fund. Meanwhile, hibah contract is used between employer and participants.